Migrant employment: a blessing in disguise from the ‘unseen’? - Farhana Izzati Yaheya; Thirunaukarasu Subramaniam (Penerbit Universiti Kebangsaan Malaysia, 2024)
Migrant workers are hired mainly to fill the demand in dirty, dangerous, and demeaning (3D) jobs in Malaysia. However, the transformation of temporary migrants into entrepreneurs while in migration, resulted in migrants’ entrepreneurship registration conundrum because they were only allowed to register for companies with private limited by shares. Currently, business registration as sole proprietors, enterprises, and limited liability partnerships are restricted to Malaysian citizens only. During the pandemic, it was observed that migrants faced heightened difficulties with marginalization and discrimination. Social media comments were captured to observe public perception towards migrants’ entrepreneurship in COVID-19 environment. A netnography analysis was conducted on eight official government agencies' Facebook pages, where 218 Facebook posts related to migrants’ entrepreneurship were observed for data collection to conduct thematic analysis. Common themes captured in the comments related to COVID-19 shaped public opinions on the topic. It was revealed that Malaysian public felt that something good resulted from COVID-19 when more enforcement measures were done during the pandemic to mitigate migrants’ enterprises. Based on thematic analysis of the comments, users criticized the lack of actions from the authorities in the past and that COVID-19 resulted in more enforcement measures due to the perceptions that migrants are responsible in spreading disease. The public has also supported such actions taken by the authority as it is seen as an opportunity to create more openings for locals to be involved in businesses especially for those who lost their jobs due to the pandemic.